Agency of the Witches and Language Play in Shakespeare’s Macbeth - Dhurjjati Sarma (Transcript: An e-Journal of Literary and Cultural Studies, 2021)
This study undertakes an analysis of Shakespeare’s Macbeth (1606) and its principal characters vis-à-vis their immediate appeal and identification with the Shakespearean audience during the first-ever performance of the play in the early years of the seventeenth century. The role of the witches (or the weird sisters) in orchestrating the destinies of the characters and also the events of the play by employing their astute and skillful use of language is a significant point of discussion in this study. In this regard, a discussion on the historical aspects of kingship and witchcraft in relation to the then king of England, James I, and on the possible impact of those factors upon the staging of the Shakespearean play Macbeth in the royal court is also carried out here. The study argues that the binaries of good and evil or light and darkness are relative categories that often feed into each other. Equivocation, as a device of language play, is analyzed here both as part of the witches’ machinations within the play and as a subterfuge for political gains by humans in the world outside it. These two worlds seem to merge into each other within the narrative of the play and thus appear before the reader/audience with all their inherent complexities and imperfections. Towards the end of this study, a brief historical overview of the refashioning of Shakespeare through adaptations and reworkings in foreign locations, particularly in India, is also provided to emphasize the allegorical and multivalent nature of his plays.